Pengaruh Karakteristik Individu Dan Pengalaman Kerja Terhadap Kepuasan Kerja Pada Kantor Camat Sebulu - Joko Sabtohadi; Ratna Wati; Johansyah Johansyah (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract :the change of the nomenclature in structure of the organization which was carried out by the local government of kabupaten kutai mammal , berdapak himself in a position officials could lose their positions that the surface has changed and placement of asn are not in accordance with the characteristics and cooperative experiences into account .In central java and the from research on offices of head of subdistricts sebulua is: 1 ) under way to find out the extent to which unsolved the individual characteristics by in also had an impact significantly correlates with much of his best work satisfaction in drinking water has; 2 ) under way to find out the extent to which unsolved cooperative experiences into account in also had an impact significantly correlates with much of his best work satisfaction in drinking water has; 3 ) under way to find out the extent to which unsolved the individual characteristics by and work experiences satisfaction in drinking water has has had a limited impact significantly correlates with civil servants at the office in kantor head of sub district sebulu; and to know the extent to which unsolved variables reaches as high as which of the the most influential satisfaction in drinking water has significantly correlates with civil servants at the office in kantor sebulu head of sub district . Metode penelitian dalam bentuk dilakukan survei , dengan menggunakan pendekatan penjelasan reseach .Kemudian hasil penelitian , 1 ) variabel karakteristik individu berpengaruh signifikan terhadap kepuasan kerja; 2 ) variabel pengalaman positif kerja berpengaruh signifikan terhadap kepuasan kerja; 3 ) karakteristik variabel individu dan pengalaman kerja secara simultan berpengaruh signifikan terhadap kepuasan kerja; dan 4 ) variabel adalah karakteristik individu variabel dominan. Keywords : Characteristic individuals, job experience, job satisfaction